Characterization and application of a crude bacterial protease to produce antioxidant hydrolysates from whey protein. Issue 1 (3rd January 2023) - Lermen, Andréia Monique; Clerici, Naiara Jacinta; Borchartt Maciel, Dienefer; Daroit, Daniel Joner
Abstract: Bacillus sp. CL14 crude protease was partially characterized and applied to obtain antioxidant whey protein isolate (WPI) hydrolysates. Optimal activity occurred at pH 9.0 and 60 °C. Ca 2+, Mg 2+, and Mn 2+ (5 mM) enhanced activity (12–26%), whereas Co 2+, Cu 2+, Fe 2+, and Zn 2+ inhibited it (50–94%). At 1% (v/v), Tween 20 and Triton X-100 enhanced activities (21–27%), β-mercaptoethanol decreased it (15%), and dimethyl sulfoxide (DMSO) had no effect. Sodium dodecyl sulfate (SDS; 0.1%, w/v) increased activity by 36%. Complete inhibition by phenylmethylsulfonyl fluoride (PMSF), and 85% inhibition by ethylenediaminotetraacetic acid, indicates its serine protease character and the importance of cations for activity/stability. With 5 mM Ca 2+, protease was optimally active at 65 °C and completely stable after 20 min at 40–55 °C. Crude protease preferentially hydrolyzed WPI and soy protein, followed by casein. WPI hydrolysis was then performed (55 °C, pH 9.0, 5 mM Ca 2+ ) for 0–180 min. Contents of trichloroacetic acid (TCA)-soluble proteins in WPI hydrolysates (HWPI) increased from 29% (0 min) to 50–52% (60–180 min), accompanied by enhanced radical scavenging activity (14%, 0 min; ∼34%, 60–180 min) and Fe 2+ -chelating ability (56%, 0 min; ∼74%, 45–180 min). CL14 protease might represent an alternative biocatalyst to obtain antioxidant hydrolysates from WPI and, potentially, from other food proteins.